Cardiac magnetic resonance assessment of cardiac involvement in autoimmune diseases - Gulhane, Avanti; Ordovas, Karen (Frontiers in Cardiovascular Medicine, 2023)
Cardiac magnetic resonance (CMR) is emerging as the modality of choice to assess early cardiovascular involvement in patients with autoimmune rheumatic diseases (ARDs) that often has a silent presentation and may lead to changes in management. Besides being reproducible and accurate for functional and volumetric assessment, the strength of CMR is its unique ability to perform myocardial tissue characterization that allows the identification of inflammation, edema, and fibrosis. Several CMR biomarkers may provide prognostic information on the severity and progression of cardiovascular involvement in patients with ARDs. In addition, CMR may add value in assessing treatment response and identification of cardiotoxicity related to therapy with immunomodulators that are commonly used to treat these conditions. In this review, we aim to discuss the following objectives: • Illustrate imaging findings of multi-parametric CMR approach in the diagnosis of cardiovascular involvement in various ARDs; • Review the CMR signatures for risk stratification, prognostication, and guiding treatment strategies in ARDs; • Describe the utility of routine and advanced CMR sequences in identifying cardiotoxicity related to immunomodulators and disease-modifying agents in ARDs; • Discuss the limitations of CMR, recent advances, current research gaps, and potential future developments in the field.